Odpowiedzi

2009-10-12T20:33:32+02:00
Y=x²-2x+3
y=2x-1
x²-2x+3=2x-1
x²-4x+4=0
(x-2)²=0
x-2=0
x=2
y=2*2-1=3
patrz zalacznik rk1
-------------------------------------------------------
y=-x²-2x+3
x+y=1→y=-x+1
-x²-2x+3=-x+1
x²+x-2=0
Δ=1+8=9 √Δ=3
x1=(-1-3)/2=-2 → y1=2+1=3 B(-2,3)
x2=(-1+3)/2=1 → y2=-1+1=0 A(1,0)
patrz zalacznik rk2
----------------------------------------------------------
y=x²+4x
x+y+4=0→y=-x-4
x²+4x=-x-4
x²+5x+4=0
Δ=25-16=9 √Δ=3
x1=(-5-3)/2=-4 → y1=4-4=0 B(-4,0)
x2=(-5+3)/2=-1 → y2=1-4=-3 A(-1,-3)
patrz zalacznik rk3
-------------------------------------------------------------
y=-x²+6x-5
y=x+5
-x²+6x-5=x+5
-x²-6x-10=0
Δ=36-40=-4
brak rozwiazan
patrz zalacznik rk4

Pozdrawiam
Hans


PS
robilem to ok 1h











1 5 1